(untitled) (Asian-Australasian Journal of Food Safety and Security, 2020)
Investigation of Aeromonas hydrophila was conducted to assess the microbial quality of broiler chickens from July to November 2019. A total of 60 samples from 20 broiler chickens were collected from two different locations of Mymensingh Sadar: KR market, Bangladesh Agricultural University (BAU) and Shesh mor bazar (10 birds from each location). Samples included 20 skins, 20 legs and 20 breast samples from 20 broiler chickens. PCR was done for the specific detection of each isolate and finally antimicrobial susceptibility testing was performed to check sensitivity pattern of each isolate. Alkaline peptone water was used for processing and enrichment of the samples followed by inoculation onto Aeromonas selective agar supplemented with ampicillin for the isolation and identification of A. hydrophila. Out of these 60 samples, 27 isolates were confirmed as A. hydrophila through biochemical tests and PCR where 55.56% isolates were recovered from Shesh mor market and other 44.4% isolates from KR market, BAU. Source-wise analysis revealed that maximum isolates of A. hydrophila were recovered from skin (59.26 %) followed by leg (22.22 %) and breast samples (18.52 %). PCR test revealed that all 27 isolates were found carrying lip gene which is specific for A. hydrophila. Isolates of A. hydrophila were found sensitive to ciprofloxacin (92%), gentamycin (66%) and chloramphenicol (50%); intermediate against erythromycin (50%), tetracycline (50%) and imipenem (50%); resistant against co-trimoxazole (84%) and ampicillin (100%). From the present study, it was found that samples were considerably contaminated with Aeromonas hydrophila causing risks for public health. Necessary control actions should be taken in every steps of production, processing and marketing for mitigation of this contamination. Asian Australas. J. Food Saf. Secur. 2020, 4(1), 22-30